2022
DOI: 10.1038/s41467-022-29503-1
|View full text |Cite
|
Sign up to set email alerts
|

The PripA-TbcrA complex-centered Rab GAP cascade facilitates macropinosome maturation in Dictyostelium

Abstract: Macropinocytosis, an evolutionarily conserved mechanism mediating nonspecific bulk uptake of extracellular fluid, has been ascribed diverse functions. How nascent macropinosomes mature after internalization remains largely unknown. By searching for proteins that localize on macropinosomes during the Rab5-to-Rab7 transition stage in Dictyostelium, we uncover a complex composed of two proteins, which we name PripA and TbcrA. We show that the Rab5-to-Rab7 conversion involves fusion of Rab5-marked early macropinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…During classical endocytosis, Rab5 accumulates at early stages and exchanges with Rab7 as the vesicles mature (Rink et al, 2005). A similar Rab5-Rab7 exchange has been described during both phagosome and macropinosome maturation at around the same time we observe PIKfyve-GFP recruitment (Kerr et al, 2006; Poteryaev et al, 2010; Tu et al, 2022; Vieira et al, 2003).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…During classical endocytosis, Rab5 accumulates at early stages and exchanges with Rab7 as the vesicles mature (Rink et al, 2005). A similar Rab5-Rab7 exchange has been described during both phagosome and macropinosome maturation at around the same time we observe PIKfyve-GFP recruitment (Kerr et al, 2006; Poteryaev et al, 2010; Tu et al, 2022; Vieira et al, 2003).…”
Section: Resultssupporting
confidence: 88%
“…Co-expression of RFP-Rab5a and GFP-Rab7A allowed us to follow the dynamics of both proteins to newly formed phagosomes in wildtype and ΔPIKfyve cells ( Figure 2A and B, Movie 3 ). In wild-type cells, as previously reported (Tu et al, 2022), RFP-Rab5A was highly enriched on perinuclear endosomes, and to a lesser extent at the plasma membrane. We also observed that RFP-Rab5A became slightly enriched at phagocytic cups just prior to closure.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To identify proteins that interact specifically with GxcM, immunoprecipitation experiment and mass spectrometry analysis were carried out as described previously with minor modification (Tu et al, 2022). Briefly, cells expressing GxcM-GFP, GxcM N790- GFP, or Teep1-GFP were starved in DB for 3 h, lysed in ice-cold lysis buffer (10 mM Hepes pH 7.2, 100 mM NaCl, 0.5% Nonidet P-40, 10% glycerol, 1 mM NaF, 0.5 mM Na 3 VO 4 , complete EDTA-free protease inhibitor (Roche), 1 mM DTT) with the addition of 15 mM EDTA, and incubated for 5 min on ice.…”
Section: Methodsmentioning
confidence: 99%